Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation Untuk Meningkatkan Aktivitas Dan Hasil Belajar IPA Pada Siswa Kelas VI SD Inpres 1 Tondo - Artini Artini; Marungkil Pasaribu; Sarjan M. Husain (Universitas Tadulako, 2015)
The main problem on this research is the low activity and learning output on the year six students elementary school (SD) Inpres 1 Tondo. Therefore, based on this problem, classroom action research has been done. The aim of this research is to implement the cooperative learning model of group investigation type. The studying focused on the main material about less energy which taught on semester II based on the program at that school. The instrument which used was lesson plans, scenario of teaching, sheets of observation activity for student and teacher, and final test at the action of cycle 2. For the results of learning output on cognitive at the pre-action average score was 65,9 the classical understanding was 65,9 and the classical completed was 52,5%. On cycle I, the average learning output score was 68,7, the classical understanding was 65,9, and 65,9% of classical understanding. On cycle II, the average csore was 88,30, and the classical completed was 87,5%. In cycle I, affective score was average 3,2 (begin to develope), in cycle II, it was 3,55 (habit). Psychomotorscore was average 3,2 (begin to develop) in cycle I and it was 3,8 (habit) in cycle II. To achieve the criterion of classical completed was influenced by the optimum of teacher and student actifity during the learning process using group investigation.